Respon Pemberian Jenis Kompos dan Dosis Pupuk Organik Cair terhadap Pertumbuhan dan Produksi Tanaman Timun Suri (Cucumis Mel L Var Reticulatus Naudin) - Sofian, Ahmad; Aminah, Iin Siti; Palmasari, Berliana; Paridawati, Ika (Jurnal Kridatama Sains dan Teknologi, 2023)
This study aims to determine how the growth and production of cucumber suri (Cucumis Mel L. Bar Reticulatus Naudin) are affected by the type of compost and the amount of liquid organic fertilizer applied. This research was conducted at AKN Sakojo No. 21 Kedondong Raye Village, Banyuasin III District, Pangkalan Balai, South Sumatra from July to September 2022. This study used a split plot randomized design consisting of nine treatment combinations and repeated three times. The first factor (Main Plot) was the variation of the type of compost, with K1 being chicken manure compost (3 kg per plot), K2 being rice straw compost (3 kg per plot), and K3 being cow manure compost (3 kg per plot). ). The second factor (subplot) was the dose of liquid organic fertilizer, with P1 being 6 cc/liter and P2 being 4 cc/liter. and 2 cc/liter is P3. The variables observed were stem length (cm), number of branches (branches), number of fruits planted (fruit), weight of fruit planted (g), weight of fruit per plot (kg). The results showed that the use of fertilizer types greatly affects the length of the plant and the number of planting branches. However, the dose of liquid organic fertilizer had a significant effect on all observed variables. The results of the analysis show that the two factors affect the variable number of planting branches through interaction. Rice straw fertilizer type treatment gave the best results on plant length and number of branches. For growth and production of cucumber suri, treatment with liquid organic fertilizer at a dose of 6 cc/l of water gives the best results. . Interaction treatment between the type of rice straw compost with a dose of liquid organic fertilizer 6 cc/l of water obtained the best results on the number of branches per plant. Keywords: Production of Suri Cucumber; Compost; liquid organic fertilizer.